Three colours trilogy : blue, white, red - Kieślowski, Krzysztof (Faber and Faber, 1998)
Krzystof Kieslowski's "Three Colors" trilogy earned him the deserved reputation as "one of the world's premier film-makers' ("Independent"). In these films, based on the colors of the French flag and the principles of liberty, equality and fraternity--the three ideals of the French Revolution--Kieslowski has crafted three parables of contemporary existence. In "Blue," Julie loses her child and husband in a car crash. In order to shield herself from the intensity of her grief, she strips away all remnants of her former life. This attempt is doomed to failure as music inexorably brings her back to a purpose in life. In "White," Karol, a Polish hairdresser, is divorced and abandoned by his beautiful French wife and finds himself destitute on the Paris streets. He meets a fellow Pole, who ingeniously smuggles him back to Warsaw in a suitcase. Working on the black market, he soon rises to the top of Poland's emerging capitalist class. Still obsessively haunted by the image of his wife, Karol sets out to make her pay the price for her betrayal. The third and final part of the trilogy, "Red," explores a strange, tentative relationship that gradualy grows between a beautiful young model and an embittered, retired judge. It is through the wisdom of her innocence that he finds the courage to engage with life again. Kieslowski brings the trilogy to a close with an event that weaves the disaparte threads into a seamless work of art.